Simulated synchrotron emission for the Tycho's supernova remnants: an asymmetric initial mass model. Issue 2 (5th March 2020) - Moranchel-Basurto, A; Velázquez, P F; Ares de Parga, G; Reynoso, E M; Schneiter, E M; Esquivel, A
ABSTRACT: We have performed 3D magnetohydrodynamics (MHD) numerical simulations with the aim of exploring the scenario in which the initial mass distribution of a supernova (SN) explosion is anisotropic. The purpose is to analyse if this scenario can also explain the radio-continuum emission and the expansion observed in young supernova remnants (SNRs). To study the expansion, synthetic polarized synchrotron emission maps were computed from the MHD simulations. We found a good agreement (under a number of assumptions) between this expansion study and previous observational results applied to Tycho's SNR, which represents a good example of asymmetric young SNRs. Additionally, both the observed morphology and the brightness distribution are qualitatively reproduced.